Survival and social reproduction strategies in angolan cities - Rodrigues, C. (Africa Today, 2007)
To survive and ensure social reproduction, families in urban Angola have developed strategies to meet the demands of daily life. The fundamental principles of these strategies are to concentrate and share resources among family members and their solidarity networks and, simultaneously, to disperse the sources and methods of generating and/or collecting these resources. Urban Angolans have proven that their efforts produce results beyond simple subsistence. The analysis of empirical data collected in Angolan cities has allowed a characterization of family strategies and an understanding of the wider motivations behind individuals' and families' efforts.